HUBUNGAN LAMA MENDERITA MORBUS HANSEN DENGAN TINGKAT DEPRESI PADA PASIEN DI PANTI REHABILITASI KUSTA NAOB KABUPATEN TIMOR TENGAH UTARA - Tiara Dirgantini; Kartini Lidia; Idawati Trisno; Ika Febrianti Buntoro (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2022)
Morbus Hansen or familiarly known as leprosy is chronic infection disease caused by the infection of Mycobacterium leprae. Leprosy patients usually tend to conceal their disease and reluctant to go to the health care facility frequently. This condition will not be able to sustain the treatment and recovery process, otherwise it will be enlarging the risks of the leprosy patients to be disabled therefore will slower the recovery process of leprosy patients.To determine the correlation between the duration of morbus hansen disease with depression level on morbus hansen patients in Panti Rehabilitasi Kusta Naob Kabupaten Timor Tengah Utara. This research uses analitical observational methods on research with cross sectional design to the patients with leprosy in Panti Rehabilitasi Kusta Naob, Timor Tengah Utara. The data is being collected by filling questionnare of Hamilton Depression Rating Scale (HDRS) by 44 leprosy patients. Sampling technique by purposive sampling technique. Result of univariate and bivariate analysis using Rank Spearman correlation test. 15,9% patients have had the disease for >6-12 months, 65,9% patients for 1-3 years and 18,2% have had the disease for >3 years. Leprosy patients without depression is 4,5%, 54,5% with mild level of depression, 36,6% with moderate depression and 4,5% with severe depression. Data analysis using Rank Spearman test correlation results in p=0,468 (p<0,05). Duration of morbus hansen disease affects the level of depression in Panti Rehabilitasi Kusta Naob Kabupaten Timor Tengah Utara